Rancang Bangun Prototipe Mesin Gravir Laser Dengan Mikrokontroler Arduino - Nanang Ali Sutisna; Hariz fauzi (Badan Kerja Sama Teknik Mesin Indonesia, 2020)
Nowaday, the use and demand of laser engraving machines is increasing for production and practical activities in vocational schools and engineeringfaculty in Indonesia. However, the price of laser engraving machine in the market is still quite high. Therefore there is a need to find a solution to overcome this problem by designing a laser engraving machine that is devoted for practical purposes at affordable prices. The control system on the laser engraving machine is designed using an Arduino Nano-based 2-axis CNC controller, with three stepper motor drive actuators, to drive the machine on the x, y, z axes and laser axis with 2500 mW of power. To prevent damage if there is a movement error, the machine is equiped with emergency stop button. The use of a control system with an Arduino nano-based 2-axis CNC microcontroller is selected on the Laser engraving machine because it is open source and more affordable. It is expected that by implementing Arduino nano ATmega328 microcontroller as a prototype, in the future the control system can be developed further so that the control system is more stable. From the results of laser engraving machine testing using laser distance parameters, laser power and laser speed motion, obtained the value of the best engraving machine parameters to be used as standard parameters.